Recruitment System for Human Resources in the Medical Records Units a Private Hospital’s Medan City in 2024 - Pradita , Desi Nur; Simanjuntak , Esraida; Ritonga , Imelda Liana; Lubis , Siti Permata Sari (Universitas Muhammadiyah Sidoarjo, 2024)
Hospital’s must provide adequate human resources to ensure optimal and high-quality health services. Establishing a medical records unit is one of the supporting efforts for health in hospitals. Managing a medical records unit that produces quality health information requires adequate resources, including human resources, facilities, and equipment. One crucial step in managing human resources effectively is recruitment. This study aims to understand the Human Resources Recruitment System for the Medical Records Unit at Private Hospitals in Medan City in 2024. This research is a qualitative study with a naturalistic approach to obtain in-depth information. The sampling technique used is purposive sampling. Data collection is done through in-depth interviews. In this study, the researcher acts as the primary research instrument, with informants 1, 2, 3, 4, 5, and 6 serving as supporting instruments using interview guides and voice recording tools (mobile phones). The research informants are HRD personnel and Heads of the Medical Records Unit at each hospital (RSU Imelda Pekerja Indonesia, RS Advent, and RSU Eshmun). The results show that there are no Standard Operating Procedures (SOPs) or policies related to the recruitment of human resources for the Medical Records Unit at the hospitals studied. The sources of job vacancy information used at the three hospitals are internal sources, and some employees do not have a background in medical record education. It is recommended that these hospitals establish SOPs or specific policies for the recruitment of human resources in the medical records unit to ensure a structured recruitment process and that recruited employees meet the qualifications in medical record education.